2017
DOI: 10.1212/wnl.0000000000004236
|View full text |Cite
|
Sign up to set email alerts
|

Automatic measurement of prosody in behavioral variant FTD

Abstract: Reduced f0 range reflects impaired prosody in bvFTD. This is associated with neuroanatomic networks implicated in language production and social disorders centered in the frontal lobe. These findings support the feasibility of automated speech analysis in frontotemporal dementia and other disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 35 publications
2
50
2
Order By: Relevance
“…The sustained ability of nonfluent patients with left frontal damage to mimic fluent speech stimuli, however, is sufficiently well established to be the basis of therapeutic trials in nfvPPA. In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency. This negative finding aligns with other research, however, and may represent differences in statistical technique, the speech elicitation task, and/or in the sample selection (e.g., bvFTD is a heterogeneous disorder, and may be prone to unrecognized differences in prosodic accommodation between subtypes).…”
Section: Discussioncontrasting
confidence: 98%
“…The sustained ability of nonfluent patients with left frontal damage to mimic fluent speech stimuli, however, is sufficiently well established to be the basis of therapeutic trials in nfvPPA. In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency. This negative finding aligns with other research, however, and may represent differences in statistical technique, the speech elicitation task, and/or in the sample selection (e.g., bvFTD is a heterogeneous disorder, and may be prone to unrecognized differences in prosodic accommodation between subtypes).…”
Section: Discussioncontrasting
confidence: 98%
“…Our finding of shorter survival time in patients with significant anterior cingulate atrophy is interesting. Behavioural features in FTD relate to brain networks involving the anterior cingulate cortex . Also, in sporadic bvFTD, anterior cingulate atrophy has been previously recognized as a predictor of disease progression and is involved early in the disease trajectory .…”
Section: Discussionmentioning
confidence: 99%
“…Regression analyses have associated poor bvFTD performance on the linguistic measures described above with this anatomic substrate. The limited range of prosodic expression found in bvFTD (Nevler et al 2017) was associated with GM atrophy of the insula and orbital regions of the right frontal lobe, areas frequently diseased in these patients. Anatomic findings in bvFTD associated poor abstract word knowledge with GM atrophy in the inferior frontal gyrus and insula bilaterally (Cousins et al 2016, 2017).…”
Section: Behavioral Variant Frontotemporal Degenerationmentioning
confidence: 93%
“…Notably, prosody also plays a role in nonemotional speech, such as the rising pitch at the end of a question requiring a yes or no response. Nevler et al (2017) conducted an acoustic analysis of a semistructured speech sample in bvFTD. The speech sample was elicited by description of a standard picture known as the cookie theft scene.…”
Section: Behavioral Variant Frontotemporal Degenerationmentioning
confidence: 99%